When medical students are autonomously motivated to mentor: a pilot study on confidence in clinical teaching and psychological well-being - Nair, Revathi; Shmon, Tori; Neufeld, Adam; McKague, Meredith; Malin, Greg (Canadian Medical Education Journal, 2024)
Introduction: Near peer mentorship (NPM) programs can help support medical students’ well-being. Most studies, however, have not accounted for students’ underlying motives to mentor, nor focused on clinical skills development and teaching. These limitations represent opportunities to better understand what motivates medical student mentors, and how to support their autonomous motivation, clinical development, and well-being. Methods: Informed by self-determination theory (SDT), we collected data from a group of medical student mentors involved in a NPM program at the University of Saskatchewan called PULSE. We then used correlation and regression to assess the relationship between students’ autonomous motivation towards mentoring, perceived competence in teaching the clinical material, and psychological well-being. Results: In line with our hypotheses, autonomous motivation towards mentoring (identified motivation in particular) was associated with higher perceived competence in clinical teaching, which in turn was associated with greater psychological well-being. Conclusions: Why medical students choose to mentor in NPM programs appears to have important implications for their clinical confidence and overall well-being. Findings are discussed in terms of designing NPM programs that support student growth and wellness in Canadian medical education.